The health status of school-age children in Barangay Ingore , La Paz, Iloilo City - Amamanglon, Keanne Paula H.; Bragancia, Ira May Joy
The study is a cross sectional survey to assess the health status of school-age children in barangay Ingore, La Paz, Iloilo City. The health status of the children was evaluated using nutritional assessment, child care practices of mothers/caretakers and past and present clinical history of disease, and respiratory function. Anthropometry and Clinical Signs were used to directly assess the nurtitional status of the children. An Interview Schedule, with mothrs/caretakers as respondents was used to determine the socio-demographic characteristics of the household to where the children belong and also to obtain information on their child health care practices. Respiratory or Lung Function was assessed using Ling Peak Flow and Chest Expansion. The results of Anthropometry using parameters for Weight-for-Age (WFA), Wight-for-Height (WFH) and Heigt-for-Age (HFA) revealed that 16.3 percent of the school-aged children were underweight; 10.7 percent were thin or wasted; 24.4 percent were stunted, and 4.0 percent were overweight/obese. The most common clinical signs indicative of malnutrition were pale conjuctiva and the occurrence of dental carries. Most of the children have been breastfed and availed of complete immunization during their pre-school age period. Almost half of them experienced childhood diseases like upper respiratory tract infections (e.g. cough, common colds, asthma, etc.) Peak flow analysis showed that among male, school-age children the average peak flow was 210.6L/minute while among female it was 195.7 L/minute. The computed peak flow was 203.2 L/minute. The average chest expansion of the subjects was 2.4 cm and the chest expansion of male and female school-age children was 2.4 centimeters. The results obtained in this study can be used as a baseline for future studies especially in the light of the recent operation of a coal-fired power plant which might affect the health status of vulnerable age groups like pre-school and school-age children.